2016
DOI: 10.1530/rep-15-0315
|View full text |Cite
|
Sign up to set email alerts
|

BMP2, 4 and 6 and BMPR1B are altered from early stages of bovine cystic ovarian disease development

Abstract: Cystic ovarian disease (COD) is an important cause of subfertility in dairy cattle. Bone morphogenetic proteins (BMPs), mainly BMP2, BMP4 and BMP6, play a key role in female fertility. In this study, we hypothesized that an altered BMP system is associated with ovarian alterations contributing to COD pathogenesis. Therefore, we examined the expression of BMP2, BMP4 and BMP6 and BMP receptor 1B (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…During folliculogenesis, the abundance of BMP2 increases in GCs of early antral follicles. Given the results of our research are according to the findings of Diaz et al [54], the expression of BMP2 in GCs was higher in antral follicles [54]. The expression pattern is concordant with the previously illustrated expression pattern of BMP2 in the ovarian somatic cells [24].…”
Section: Discussionsupporting
confidence: 92%
“…During folliculogenesis, the abundance of BMP2 increases in GCs of early antral follicles. Given the results of our research are according to the findings of Diaz et al [54], the expression of BMP2 in GCs was higher in antral follicles [54]. The expression pattern is concordant with the previously illustrated expression pattern of BMP2 in the ovarian somatic cells [24].…”
Section: Discussionsupporting
confidence: 92%
“…Although ACVR2 binds activins, it has been found that ACVR2B also binds inhibin A/B, and BMP2, 6 and 7 (Caestecker, ). Results found by Díaz et al () indicated an alteration in the expression of BMPs in cows with COD, especially a higher expression of BMP4 and BMP6 as well as of BMPR1B, which occurs early in folliculogenesis and incipiently during the development of the disease. Consequently, we can hypothesize that high expression of these ligands and their receptors in ovarian structures of cows with COD exacerbates the function of these ligands.…”
Section: Discussionmentioning
confidence: 93%
“…Although ACVR2 binds activins, it has been found that ACVR2B also binds inhibin A/B, and BMP2, 6 and 7 (Caestecker, 2004). Results found by Díaz et al (2016) indicated an alteration in the expression of BMPs in cows with COD, especially a higher expression of BMP4 and BMP6…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations